The Role of Islamic Religious Education in Building Tolerance between Religious People - Supadi, Ari (CV. Tripe Konsultan, 2024)
This research aims to analyze the role of Islamic Religious Education (PAI) in building tolerance between religious communities in Indonesia. Tolerance between religious communities is an important aspect in maintaining social harmony and harmony in a country as diverse as Indonesia. The research method used in this research is a qualitative approach with descriptive technical analysis. Data was collected through interviews with PAI teachers, observations in schools, as well as reviewing Islamic Religious Education curriculum documents. The research results show that Islamic Religious Education has a significant role in building an attitude of tolerance among students, through emphasizing the values of Islamic teachings which teach peace, mutual respect and respect for differences. However, implementing a curriculum that focuses more on ritual aspects still reduces the effectiveness of teaching the values of tolerance. This research recommends increasing the integration of tolerance values in the PAI curriculum as well as training for teachers to develop approaches that are more inclusive and based on dialogue between diverse communities. It is hoped that with these efforts, Islamic Religious Education can become an important agent in creating a more tolerant and harmonious society.